Incidence of Cacao Frosty Pod Rot in a Tree of the Clone CCN – 51 Exposed to a Concentrated Infection Source Originating of the Ground - Gabriel Cubillos; Nelson Ardila (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 8, 2023)
The impact of an infection ground source of Cacao frosty pod rot (Moniliophthora roreri (Cif. & Par.) Evans et al. was determined through the incidence of the disease in a tree of cacao from clone CCN - 51. For this purpose, the source of infection compounded by 27 diseased fruits, of which 24 were in a profuse degree of sporulation, was introduced and deposited into 50 cm. around of the tree in question. Every seven days, were made observations on the evolution of the disease and were collected the healthy and diseased fruits present on the tree. Two months and 10 days after the source of infection was introduced, only 1 fruit with Frosty pod rot was collected, attributable to external sources since it was found seven days after the source of infection was placed. Once again it was proved that diseased fruits deposited on the soil have no importance in the generation of epidemics of Moniliphthora roreri.